2014
DOI: 10.1530/jme-13-0200
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4 stimulates islet cell replication via the IGF1 receptor activation of mTORC1/S6K1

Abstract: Glucagon-like peptide 1 receptor (GLP1R) agonists, such as exendin-4, potentiate glucosestimulated insulin secretion and are currently used in the management of type 2 diabetes. Interestingly, GLP1R agonists also have the ability to augment b-cell mass. In this report, we provide evidence that in the presence of glucose, exendin-4 stimulates rodent islet cell DNA replication via the activation of ribosomal protein S6 kinase 1 (S6K1) and that this is mediated by the protein kinase B (PKB)-dependent activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 55 publications
3
11
1
Order By: Relevance
“…In conclusion, the System-L transporter LAT1 plays an important role in islet cell proliferation and insulin secretion. Although a reduction in LAT1 expression decreases mTORC1 activation, and findings from others and our studies have shown that mTORC1 is required for β-cell proliferation (Balcazar et al 2009, Xie et al 2014, it is difficult to confirm whether the effects of reducing LAT1 expression on proliferation is indeed mediated by the inhibition of mTORC1. However, these effects are unlikely due to the potential positive effects of leucine on insulin secretion, as these experiments were carried out in nutrientrich media containing a high concentration of glucose.…”
Section: Lat1 Plays An Important Role In Islet Function and Proliferacontrasting
confidence: 72%
See 2 more Smart Citations
“…In conclusion, the System-L transporter LAT1 plays an important role in islet cell proliferation and insulin secretion. Although a reduction in LAT1 expression decreases mTORC1 activation, and findings from others and our studies have shown that mTORC1 is required for β-cell proliferation (Balcazar et al 2009, Xie et al 2014, it is difficult to confirm whether the effects of reducing LAT1 expression on proliferation is indeed mediated by the inhibition of mTORC1. However, these effects are unlikely due to the potential positive effects of leucine on insulin secretion, as these experiments were carried out in nutrientrich media containing a high concentration of glucose.…”
Section: Lat1 Plays An Important Role In Islet Function and Proliferacontrasting
confidence: 72%
“…Rat islet cell proliferation assays were performed essentially as described previously (Kwon et al 2006, Xie et al 2014. A total of 150 rat islets of Langerhans per treatment were used for proliferation assay.…”
Section: Proliferation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…However, to our surprise, Lrp1-βKO islets after HFD exhibited a paradoxical increase in p85 S6K1 phosphorylation ( Figure 5A and Supplemental Figure 4, A-D). Such changes did not fully transmit to S6 phosphorylation ( Figure 5A and Supplemental Figure 4E), which depends primarily on S6K2 or p70 S6K1 (23)(24)(25). Instead, S6K1 activation can contribute, at least in part, to the suppression of IRS-2 as feedback inhibition (26) and, eventually, the failureof β cells to compensate (27,28).…”
Section: Resultsmentioning
confidence: 99%
“…We inferred that these effects are probably owing to the saturability of the receptor. Most studies report that the effective concentrations of GLP1 or exendin-4 for different cell lines are between 10 −9 and 10 −6 M (Sanz et al 2010, Heller et al 2011, Xie et al 2014 dosage range of exendin-4 for osteoblast proliferation, with a maximum effective dose of 10 −7 M. The optimum treatment time of 48 h may be attributable to a number of factors, including the half-life of exendin-4 and a corresponding decrease in bio-utilization of the drug, as well as increased cell apoptosis given the limited volume of the cell culture plates used in this study.…”
Section: Figurementioning
confidence: 99%